Find the Slope and Y-Intercept (-12,7) , (-10,-4)

Math
(-12,7) , (-10,-4)
Find the value of the slope.
Tap for more steps…
Slope is equal to the change in y over the change in x, or rise over run.
m=change in ychange in x
The change in x is equal to the difference in x-coordinates (also called run), and the change in y is equal to the difference in y-coordinates (also called rise).
m=y2-y1x2-x1
Substitute in the values of x and y into the equation to find the slope.
m=-4-(7)-10-(-12)
Simplify.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Multiply -1 by 7.
m=-4-7-10-(-12)
Subtract 7 from -4.
m=-11-10-(-12)
m=-11-10-(-12)
Simplify the denominator.
Tap for more steps…
Multiply -1 by -12.
m=-11-10+12
Add -10 and 12.
m=-112
m=-112
Move the negative in front of the fraction.
m=-112
m=-112
m=-112
Find the value of the y-intercept.
Tap for more steps…
Substitute the value of m into the slope-intercept form of the equation, y=mx+b.
y=(-112)⋅x+b
Substitute the value of x into the slope-intercept form of the equation, y=mx+b.
y=(-112)⋅(-12)+b
Substitute the value of y into the slope-intercept form of the equation, y=mx+b.
7=(-112)⋅(-12)+b
Rewrite the equation as (-112)⋅(-12)+b=7.
(-112)⋅(-12)+b=7
Simplify each term.
Tap for more steps…
Cancel the common factor of 2.
Tap for more steps…
Move the leading negative in -112 into the numerator.
-112⋅-12+b=7
Factor 2 out of -12.
-112⋅(2(-6))+b=7
Cancel the common factor.
-112⋅(2⋅-6)+b=7
Rewrite the expression.
-11⋅-6+b=7
-11⋅-6+b=7
Multiply -11 by -6.
66+b=7
66+b=7
Move all terms not containing b to the right side of the equation.
Tap for more steps…
Subtract 66 from both sides of the equation.
b=7-66
Subtract 66 from 7.
b=-59
b=-59
b=-59
The values of the slope and y-intercept are m=-112 and b=-59.
m=-112
b=-59
Find the Slope and Y-Intercept (-12,7) , (-10,-4)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top